2016
DOI: 10.3390/ijms17091474
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Preoperative Serum Aspartate Aminotransferase (AST) Level on the Prognosis of Patients with Non-Small Cell Lung Cancer

Abstract: The purpose of this work is to analyze preoperative serum aspartate aminotransferase (AST) levels and their effect on the prognosis of patients with non-small cell lung cancer (NSCLC) after surgical operation. These analyses were performed retrospectively in patients with NSCLC followed by surgery; participants were recruited between January 2004 and January 2008. All clinical information and laboratory results were collected from medical records. We explored the association between preoperative serum AST and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 26 publications
2
30
2
Order By: Relevance
“…In-depth studies determined that APRI also had potential prognostic value and could be used as a stable marker to predict the outcome of patients with HCC 1113. It has been known that AST and PLT play an important role in tumor progression and are associated with prognosis in several human cancers, including HCC 15,30,31. APRI is a combination of the above two predictors, and it is low in cost and more easily detectable.…”
Section: Discussionmentioning
confidence: 99%
“…In-depth studies determined that APRI also had potential prognostic value and could be used as a stable marker to predict the outcome of patients with HCC 1113. It has been known that AST and PLT play an important role in tumor progression and are associated with prognosis in several human cancers, including HCC 15,30,31. APRI is a combination of the above two predictors, and it is low in cost and more easily detectable.…”
Section: Discussionmentioning
confidence: 99%
“…If any of these tissues are damaged, AST will be released into the bloodstream [12,13]. While increased AST levels are indicative of a tissue injury, it is not speci c to the liver per se [14,15]. By contrast, ALT is found primarily in the liver.…”
Section: Resultsmentioning
confidence: 99%
“…CAT functions as AST in MAS, allowing electron transfer from NADH through the mitochondrial electron transfer chain, intersecting with glycolysis, which suggests it can have important roles in the cancer context. However, the impact of AST on cancer cells still remains unclear [ 68 ]. Bayomi and colleagues reported that increased serum CAT levels correlate with cyclooxygenase 2 (COX-2)-encoding ( COX2 ) mRNA expression in hepatocellular carcinoma [ 69 ].…”
Section: Cat Role In Physiology and In Cancermentioning
confidence: 99%